2006
DOI: 10.1002/bit.21080
|View full text |Cite
|
Sign up to set email alerts
|

An exclusion mechanism in ion exchange chromatography

Abstract: Protein dynamic binding capacities on ion exchange resins are typically expected to decrease with increasing conductivity and decreasing protein charge. There are, however, conditions where capacity increases with increasing conductivity and decreasing protein charge. Capacity measurements on two different commercial ion exchange resins with three different monoclonal antibodies at various pH and conductivities exhibited two domains. In the first domain, the capacity unexpectedly increased with increasing cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
107
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(124 citation statements)
references
References 36 publications
15
107
2
Order By: Relevance
“…Zydney the rate of protein mass transfer into the particle at low conductivity and low pH observed by Harinarayan et al (2006) and Faude et al (2007).…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…Zydney the rate of protein mass transfer into the particle at low conductivity and low pH observed by Harinarayan et al (2006) and Faude et al (2007).…”
Section: Introductionmentioning
confidence: 96%
“…Recent studies of dynamic-binding capacities for several monoclonal antibodies in SP Sepharose TM XL and SP Sepharose Fast Flow cation exchange resins showed a significant reduction in dynamic-binding capacity at very low ionic strength and low pH (Harinarayan et al, 2006) conditions that would have been expected to generate the greatest electrostatic attraction between the positively charged proteins and the negatively charged resin. Confocal scanning laser microscopy demonstrated that this reduction in dynamic-capacity was caused by a dramatic reduction in mass transfer rates within the porous cation exchange particles, with the antibodies penetrating only a few microns into the particle interior under low ionic strength conditions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…CLSM provides the visualisation of an intraparticle protein distribution (i.e., an inhomogeneous protein density) without mechanical destruction of the resin particle and explanation of absorption and diffusion mechanisms inside many chromatographic absorbents. There is a reach literature on CLSMbased chromatography, see, e.g., Ljunglöf and Hjorth (1996); Ljunglöf and Thömmes (1998); Linden et al (1999); Dziennik et al (2003); Hubbuch et al (2003); Kasche et al (2003); Harinarayan et al (2006); Kavoosi et al (2007); Langford et al (2007); Ljunglöf et al (2007); Susanto et al (2007).…”
Section: Introductionmentioning
confidence: 99%